(3GdYed h GdCSQI (B: s (3OQGSI dCfeGW GdJhajb Hjf GdYed GdeCLhQ h GdMjGI GdYGFdjI ai eUQ (B/ s - (3CMeO HOQ eMeO SjOs; (3GdSYjO UGHQ GdeUQi (B: s; (3Ydi eMeO GdecGhi (B: s ((3GdbGgQI (B: s (3CMeO HOQ eMeO SjO (B: s, 2020)
(3JSYi GdOQGSI GdMGdjI ddcTa Yf WHjYI GdCfeGW GdJi jdLC EdjgG GdCRhGL h GdRhLGJ ai eUQ ddJhajb Hjf eJWdHGJ GdMjGI GdegfjI ef LGfH(B: (3hGdGdJRGeGJ GdJi JaQVgG Ydjge GdMjGI GdYGFdjI ef LGfH BNQ(B. (3h JfWdb GdOQGSI ef GdGaJQGV HCf GdChVGY GdGLJeGYjI h GdGbJUGOjI h GdKbGajI ai eUQ oJSge ai JTocd CfeGW eNJdaI ef GdEYGdI(B: (3jSJWjY ef NdGdgG GdCRhGL h GdRhLGJ GdLeY Hjf eJWdHGJ GdMjGJjf GdegfjI h GdCSQjI(B: (3dcf gPg GdCfeGW JJHGjf h JNJda ef MjK OQLI eTGQcJge ai GdCYeGd GdeCLhQI(B: (3h GdCYeGd GdefRdjI h GdQYGFjI ZjQ GdeCLhQI(B. (3h HGSJNOGe efgL OQGSI GdMGdI(B: (3GdPi CJGM EecGfjI GdGYJeGO Ydi YOI COhGJ efgLjI cGdebGHdGJ GdeJYebI(B: (3h GdedGMXI ai LeY GdHjGfGJ ef (B33 (3CSQI eYjTjI OGNd Ebdje GdbGgQI GdcHQi GdMVQi(B: (3cTaJ fJGFL GdOQGSI Yf TjhY CQHYI CfeGW ddJhajb Hjf GdYed h GdCSQI gi GdEYGdI GdfSGFjI(B: (3h GdPchQjI(B: (3h GdJhGabjI(B: (3h GdJTGQcjI(B. (3h bO GJVM ef GdfJGFL Cf GdCfeGW GdKdGKI GdChdi JNOe GdMjGI GdYGFdjI HOQLI CcHQ ef GdMjGI GdGbJUGOjI(B: (3HjfeG ojYO feW GdEYGdI GdJTGQcjI hGMkOG ef GdCfeGW GdJi ef Gdeecf Cf nJNOe YedjI GdJfejI GdGbJUGOjI ai eUQ EPG eG GoJNPJ GdELQGAGJ h GdJOGHjQ GdMchejI GdOGYeI dgPG GdfeW ef GdEYGdIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GdELJeGYs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCSQI s; (3GdYeds; (3GdYed GdeCLhQ s